THE EFFECTIVENESS OF SPECIAL ARRANGEMENTS AND BASIC AGREEMENTS IN OVERCOMING STATELESSNESS ISSUES AT THE BORDER BETWEEN INDONESIA AND PAPUA NEW GUINEA - Pulung Widhi Hananto; Rahandy Rizki Prananda; Ratna Herawati; Irawati Irawati (Masalah-Masalah Hukum, 2022)
Differences in perspective on territorial boundaries between local communities with customary rights based on customary law and the definition of territorial boundaries in the context of state administration raises a dilemma, one of which is the potential for statelessness. The existence of ulayat customary land is a factor that affects illegal border crossings. The Governments of the Republic of Indonesia and Papua New Guinea responded to this by entering into basic agreements and special arrangements. This article aims to examine the implementation and effectiveness of special arrangements and basic agreements in dealing with the emergence of statelessness problems. This study uses a statutory and conceptual approach. The results of the study found that the application of rules that were positivistic in nature could not be applied absolutely to residents of the border between Indonesia and Papua New Guinea. The use of red and yellow card policies is only temporary, so a permanent policy is needed to address this issue.